PENGEMBANGAN MODEL PEMBELAJARAN “PROMISTER” UNTUK MENINGKATKAN HASIL BELAJAR WAYANG PANDHAWA PADA SISWA SEKOLAH DASAR - Istiningsih, Galih; Alawiyah, Ela Minchah; Priharlina, Evik (Jurnal Holistika, 2018)
ABSTRACTThis study departs from the problem of the still low quality of the process of learning Javanese language, one of which is the wayang pandhawa and the ability of the teacher to integrate character values in classroom learning. The main objective of this year I study was to produce innovative learning models based on Multiple Character Intelligence (PROMISTER) projects that had obtained material and learning expert validation.Research uses research and development methods or "Research and Development" (R & D) with the following steps: a) conducting preliminary research, b) planning, c) developing prototype learning models include: needs analysis of Javanese language learning models and prototypes PROMISTER learning model, d) expert test The research subjects were taken as many as 4 schools in Magelang Regency. Respondents from each school involved fourth grade teachers, fourth grade students, and elementary school principals. The subject of this study also involved 2 material experts, and 2 experts in the learning model. The sampling technique was purposive sampling. Keywords:  Promister, Result of Pandhawa Wayang Learning    ABSTRAKPenelitian ini berangkat dari permasalahan masih rendahnya kualitas proses pembelajaran bahasa Jawa salah satunya wayang pandhawa dan kemampuan guru dalam mengintegrasikan nilai-nilai karakter dalam pembelajaran di kelas. Tujuan utama penelitian tahun I ini adalah untuk menghasilkan model pembelajaran inovatif Proyek berbasis Multiple Intellegence  Berkarakter (PROMISTER) yang telah mendapatkan validasi ahli materi dan pembelajaran. Penelitian menggunakan metode penelitian dan pengembangan atau “Research and Development” (R & D) dengan langkah-langkah sebagai berikut: a) melakukan penelitian pendahuluan, b) perencanaan, c) pengembangan prototipe model pembelajaran) uji ahli Subjek penelitian diambil sebanyak 4 sekolah  di Kabupaten Magelang. Responden dari setiap sekolah melibatkan guru kelas IV, murid kelas IV, dan kepala sekolah SD. Subjek penelitian ini juga melibatkan 2 orang ahli materi, dan 2 orang ahli model pembelajaran. Teknik pengambilan sampel secara purposive sampling. Kata kunci: Promister, hasil Belajar Wayang Pandhawa